Quality of life among hemodialysis patients in a referral center in Kathmandu: A mixed method study - Shanti Gurung; Nishchal Devkota (PLoS ONE, 2025)
Introduction Chronic kidney disease (CKD) affects about 10% of people worldwide, with rising cases in Nepal. Late diagnosis and limited healthcare access worsen patients’ quality of life (QoL), causing physical symptoms and emotional distress. Financial strain and travel difficulties further burden Nepalese patients on dialysis. While medical treatments address physical issues, mental and social well-being remain overlooked. This mixed-method study explores factors affecting QoL and patients lived experiences, aiming to improve patient-centered care in Nepal. Methods This convergent parallel mixed-method study was conducted at the National Kidney Center in Kathmandu, Nepal, involving adult hemodialysis patients. A quantitative survey of 260 participants was conducted, and 15 purposively selected patients took part in an in-depth qualitative interview until data saturation. Data were collected simultaneously during dialysis sessions using validated Nepali versions of the KDQOL-36 and socio-demographic questionnaires. Quantitative data were analyzed with descriptive and non-parametric tests in SPSS, while qualitative data were transcribed, translated, and thematically coded based on KDQOL domains using a phenomenological approach. Ethical approval was obtained, and informed consent was secured from all participants, ensuring confidentiality and voluntary participation. Results This study examined CKD patients on hemodialysis. Most were male (64.2%), married (76.5%), and in advanced stage of CKD. Treatment burden was reported by 74.2%. Median symptom score was 66.67; physical and mental health median scores were 32.62 and 39.40. Males and those with lower education reported higher burden. Socio-economic status and financial strain significantly affected outcomes. No significant differences were found by marital status, diet, or CKD duration. Patients on hemodialysis experienced significant symptom burden, including fatigue, weight loss, pain, and mobility issues, leading to dependency and emotional distress. Mental health challenges, such as anxiety, depression, and fear of the future, were common, especially among those with financial strain. Family and social support, acceptance, and coping strategies helped some maintain resilience. Socio-economic status was strongly linked to symptom severity and quality of life, emphasizing the need for holistic support in care. Conclusion For hemodialysis patients in Nepal, managing physical symptoms is only part of the struggle; emotional distress, financial pressure, and loss of independence weigh more heavily. These burdens are intensified by limited mental health support, financial security, and access to decentralized care. Addressing these challenges requires a compassionate, patient-centered approach that goes beyond survival; supporting dignity, emotional well-being, and a better quality of daily life.